Biosolids as fertilizer in the tomato crop - Castellanos-Rozo, José; Galvis-López, Jaqueline; Manjarres , Elsa; Merchán-Castellanos, Nuri (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The sludge produced in wastewater treatment plants constitutes a potential alternative to replace traditional fertilizers and reduce costs in agricultural activities. The objective of this work was to compare the fertilizing effect of the sludge produced in the wastewater treatment plant of Sotaquirá-Colombia, with the fertilizers traditionally used on the tomato crop (Solanum lycopersicum L). For this, the sludge was previously stabilized with two different treatments: dehydration and the addition of CaO. Subsequently, four treatments were applied to the tomato seedlings, 135 g.kg-1 of dehydrated biosolid, 135 g.kg-1 biosolid stabilized with CaO, 135 g.kg-1 of ABIMGRA®, 135 g.kg-1 of naturcomplet®-G, and greenhouse soil without biosolids. The height of the plant, the fresh and dry mass, foliar area, and fruits per plant, were measured at 0, 30, 60 and 90 days after sowing. In tomato fruits, the concentrations of heavy metals, coliforms, helminth eggs, somatic phages, and Salmonella sp., were determined. The dehydrated biosolids had a significant effect on the size, the fresh mass, foliar area, and the number of fruits per plant, compared to the alkaline biosolids. The dry mass of the plants (120 g. plant-1) was similar to traditional fertilizers and biosolids. Tomatoes produced with biosolids had low levels of heavy metals and an absence of pathogenic microorganisms. In conclusion, the biosolid obtained by dehydration in Sotaquirá can be used as a potential fertilizer in tomato cultivation.